2009
DOI: 10.1111/j.1469-1795.2008.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious effects by mosquitofish (Gambusia affinis) on the endangered fire salamander (Salamandra infraimmaculata)

Abstract: Invasive fishes, via competition and predation, may be an important factor in endangering populations of amphibians and other aquatic fauna. The mosquitofish, Gambusia affinis, commonly stocked into amphibian breeding sites for mosquito control worldwide, has recently been found in some breeding sites of the endangered fire salamander Salamandra infraimmaculata in northern Israel. A comparison of Salamandra larvae in natural pools varying in Gambusia densities suggested that Gambusia negatively affects Salaman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 45 publications
1
37
0
1
Order By: Relevance
“…For example, Nile tilapia (Oreochromis niloticus) was capable of modifying nutrient regimes by increasing nitrogen and phosphorus availability via excretion, promoting algae growth, and contributing to eutrophication of a reservoir of Brazil (Figueredo and Giani 2005). The mosquitofish (Gambusia affinis) has been reported to be responsible for the decline and extinction of some fish (Galat and Robertson 1992) and amphibian (Gamradt and Kats 1996;Segev et al 2009;Karraker et al 2010) species in North American and Asia. Competition between non-native and native salmonids has led to extinction or significant population decreases in Europe (Hasegawa and Maekawa 2006;Fausch 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nile tilapia (Oreochromis niloticus) was capable of modifying nutrient regimes by increasing nitrogen and phosphorus availability via excretion, promoting algae growth, and contributing to eutrophication of a reservoir of Brazil (Figueredo and Giani 2005). The mosquitofish (Gambusia affinis) has been reported to be responsible for the decline and extinction of some fish (Galat and Robertson 1992) and amphibian (Gamradt and Kats 1996;Segev et al 2009;Karraker et al 2010) species in North American and Asia. Competition between non-native and native salmonids has led to extinction or significant population decreases in Europe (Hasegawa and Maekawa 2006;Fausch 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Introduced populations of D r a f t mosquitofish alter food webs (Pyke 2008) and negatively affect amphibians and fishes (Blanco et al 2004;Zeiber et al 2008;Segev et al 2009;Drake et al 2014;Shulse and Semlitsch 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Amphibians are especially vulnerable to the introduction of new predators because they often have complex life cycles with aquatic eggs and larvae (Kats and Ferrer 2003;Vonesh 2005;Segev et al 2009;Smith et al 2013), which are consumed in large amounts by aquatic alien predators (G. affinis, Goodsell and Kats 1999;Gambusia holbrooki, Stanback 2010; Pomacea canaliculata, Karraker and Dudgeon 2014; P. clarkii, Polo-Cavia and Gomez-Mestre 2014). The western mosquitofish G. affinis (Poeciliidae), one of the 100 worst invasive species listed by the World Conservation Union, is native to the fresh waters of the eastern and southern United States (Lowe et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Its widespread introduction can be attributed to its purported effectiveness in consuming larval mosquitoes (Pyke 2008). Previous studies have shown that G. affinis readily preys on amphibian eggs and larvae, both within (Walls et al 2002;Baber and Babbitt 2003;Zeiber et al 2008) and outside of its native range (Goodsell and Kats 1999;Komak and Crossland 2000;Segev et al 2009;Shulse and Semlitsch 2014;Fan et al 2016). G. affinis was introduced to China for mosquito control in 1927, and it now occurs throughout the southern water bodies of the Yangtze River (Li and Jie 2002).…”
Section: Introductionmentioning
confidence: 99%